Toward an evaluation model for transnational cooperation activities in rural areas: a case study within an EU LEADER project - De Luca Anna Irene; Iofrida Nathalie; Gulisano Giovanni; Strano Alfio (Bulletin of Geography. Socio-Economic Series)
Cooperation activities between Local Action Groups (LAGs) have been introduced into EU LEADER (Liaison Entre Actions de Développement de l’Économie Rurale) initiative to provide rural areas the opportunity to exchange experiences and best practices, as well as to realize common activities by pooling human and financial resources. The main purposes are to overcome isolation and add value to local development strategies. The benefits of cooperation are widely recognized but, undeniably, it can be also a difficult and time-consuming process. For this reason, evaluation is a necessary tool to measure the success of cooperation and to help actors address their strategies for the future. In this paper, an evaluation methodology is proposed and applied to an EU LEADER+ case study, the ‘Integrated Project for Rural Tourism: Environment and Qualified Hospitality’, a transnational cooperation experience led by LAG Aspromar, based in the province of Reggio Calabria, Southern Italy. Quantitative and qualitative data have been collected through the integration of three typical methods of social research: two techniques based on surveys, namely interviews with privileged actors, and a semi-structured questionnaire, and a technique based on non-survey data and the study of documents. Results can be useful to highlight pros and cons of the management of a cooperation project and to stimulate projects’ leaders on activating improvement processes.